1986
DOI: 10.1172/jci112622
|View full text |Cite
|
Sign up to set email alerts
|

Embryotoxic effects of brief maternal insulin-hypoglycemia during organogenesis in the rat.

Abstract: To test whether maternal hypoglycemia can impair organogenesis, we induced brief glucopenia with insulin in conscious pregnant rats during either the headfold stage or the early neural tube closure stage of embryogenesis. At each time, 10 pairs of animals received identical insulin infusions for 1 h. Half the animals were maintained at euglycemia during the infusions, while the others were allowed to become hypoglycemic. Euglycemia was maintained or restored in all animals immediately after the insulin was sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(32 citation statements)
references
References 46 publications
2
29
0
1
Order By: Relevance
“…The potential consequences of placental transfer include the risk of neonatal hyperinsulinemia and hypoglycemia. Animal studies suggest that hypoglycemia may cause teratogenesis (12). There has been a recent report of congenital anomalies in the off-spring of two women taking insulin lispro throughout pregnancy, despite optimal glycemic control (13).…”
mentioning
confidence: 99%
“…The potential consequences of placental transfer include the risk of neonatal hyperinsulinemia and hypoglycemia. Animal studies suggest that hypoglycemia may cause teratogenesis (12). There has been a recent report of congenital anomalies in the off-spring of two women taking insulin lispro throughout pregnancy, despite optimal glycemic control (13).…”
mentioning
confidence: 99%
“…It has been suggested that this may explain why the incidence of macrosomia continues to be increased, despite excellent HbA 1c levels throughout pregnancy (5,6). From animal studies (in rodents), there is strong evidence that hypoglycemia occurring early in gestation might be teratogenic (7,8).…”
mentioning
confidence: 99%
“…Low maternal glucose levels, which can result from stringent metabolic control of pregnant diabetic women (23), have also been suggested, on the basis of studies with pregnant animals and embryo cultures (24,27), to adversely affect development. The results reported here show that low glucose levels, like high levels, directly impair the biosynthesis of sulfated proteoglycans in developing cartilage and are thus potentially teratogenic.…”
Section: Discussionmentioning
confidence: 99%
“…However, stringent metabolic control of insulin-treated diabetic women during pregnancy may expose patients to frequent hypoglycemia (23), which is also of concern as a risk factor in fetal development (15,24). Experimental studies of pregnant animals, and embryos in organ culture, indicate teratogenic consequences of both hyper- (10,25,26) and hypoglycemia (15,16,27,28).…”
mentioning
confidence: 99%